Imaging cell morphology and physiology using X-rays. (5th April 2019) - Weinhardt, Venera; Chen, Jian-Hua; Ekman, Axel; McDermott, Gerry; Le Gros, Mark A.; Larabell, Carolyn
Abstract : Morphometric measurements, such as quantifying cell shape, characterizing sub-cellular organization, and probing cell–cell interactions, are fundamental in cell biology and clinical medicine. Until quite recently, the main source of morphometric data on cells has been light- and electron-based microscope images. However, many technological advances have propelled X-ray microscopy into becoming another source of high-quality morphometric information. Here, we review the status of X-ray microscopy as a quantitative biological imaging modality. We also describe the combination of X-ray microscopy data with information from other modalities to generate polychromatic views of biological systems. For example, the amalgamation of molecular localization data, from fluorescence microscopy or spectromicroscopy, with structural information from X-ray tomography. This combination of data from the same specimen generates a more complete picture of the system than that can be obtained by a single microscopy method. Such multimodal combinations greatly enhance our understanding of biology by combining physiological and morphological data to create models that more accurately reflect the complexities of life.